2020
DOI: 10.1097/wco.0000000000000839
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high field 7 T imaging in multiple sclerosis

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Other 7T SWI reports exist of visualization of vascular anomalies such as cavernous malformations with associated developmental venous anomalies, 29,30 radiation-induced microbleeds, [31][32][33] iron deposition in multiple sclerosis lesions, [34][35][36] substantia nigra in Parkinson disease, 37 other degenerative diseases, 38 and senile plaquelike lesions in patients with Alzheimer disease. 14 In the present study, we found that the same postprocessing methods were optimal for visualization of the corticomedullary junction and the small vasculature of gliomas.…”
Section: Application Of 7t Swi In Assessment Of Brain Tumors and Othe...mentioning
confidence: 99%
“…Other 7T SWI reports exist of visualization of vascular anomalies such as cavernous malformations with associated developmental venous anomalies, 29,30 radiation-induced microbleeds, [31][32][33] iron deposition in multiple sclerosis lesions, [34][35][36] substantia nigra in Parkinson disease, 37 other degenerative diseases, 38 and senile plaquelike lesions in patients with Alzheimer disease. 14 In the present study, we found that the same postprocessing methods were optimal for visualization of the corticomedullary junction and the small vasculature of gliomas.…”
Section: Application Of 7t Swi In Assessment Of Brain Tumors and Othe...mentioning
confidence: 99%
“…A 2020 study showed that, compared to 3 T, 7 T scanners have up to 134% higher sensitivity for lesion detection. This led to better discrimination between cortical and WM lesions, and between leukocortical and WM lesions within the cerebellum in pwMS [64]. However, while lesion characterisation and volumetric MRI measures at all field strengths are useful for assessing structural changes associated with MS disease activity, they do not address any changes in FC or activity.…”
Section: Lesion and Volumetric Mrimentioning
confidence: 99%
“…The contribution of 7-T MRI for detecting MS white matter lesions is less robust than that for the cortex [ 43 ] with ongoing research in the optimization of sequences to reduce limitations secondary to high SAR and to reduce RF field inhomogeneities [ 43 45 ]. T2*, FLAIR, magnetization transfer imaging, and magnetization-prepared rapid gradient-echo have been suggested as currently recommended sequences to visualize white matter lesions at 7 T [ 43 , 46 , 47 ].…”
Section: Ultrahigh Field Mrimentioning
confidence: 99%
“…This observation lends support to CSF-mediated pathogenic mechanisms in lesion development that may differ between MS subtypes. Despite the potential theoretical benefits of imaging the spinal cord in MS at ultrahigh field, technical challenges remain, including the lack of dedicated RF coils that may compromise image quality; small variations in tissue susceptibility that are enhanced at 7 T; and motion artifacts due to respiration, cardiac movement, swallowing and CSF flow [ 32 , 43 ].…”
Section: Ultrahigh Field Mrimentioning
confidence: 99%